2000
DOI: 10.1002/1098-1004(200007)16:1<49::aid-humu9>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

3′ polymorphisms of ETS1 are associated with different clinical phenotypes in SLE

Abstract: A microsatellite repeat polymorphism was identified in the 3' flanking region of the human ETS1 gene. Sequencing revealed two CA repeat segments in close proximity. Seven different alleles comprising various combinations of CA repeat units were identified in a healthy control population. Because ETS1 plays a role in lymphocyte development and function, apoptosis, and inflammation, we examined whether any of these polymorphisms were associated with a systemic inflammatory condition, systemic lupus erythematosus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…These two polymorphisms were also revealed to predispose different ethnic groups to different immune diseases (20). In addition, an allele of a microsatellite repeat polymorphism in the 3 0 flanking region of the ETS1 gene, even though it was mainly found in Caucasian individuals compared to African Americans, has been associated with vasculitis mainly in African American SLE patients (8). These findings seem to indicate that different linkage disequilibrium patterns of the ETS1 polymorphisms studied, along with other adjacent or non-adjacent ETS1 variants, or with polymorphisms of other relevant genes may predispose different ethnic groups to autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two polymorphisms were also revealed to predispose different ethnic groups to different immune diseases (20). In addition, an allele of a microsatellite repeat polymorphism in the 3 0 flanking region of the ETS1 gene, even though it was mainly found in Caucasian individuals compared to African Americans, has been associated with vasculitis mainly in African American SLE patients (8). These findings seem to indicate that different linkage disequilibrium patterns of the ETS1 polymorphisms studied, along with other adjacent or non-adjacent ETS1 variants, or with polymorphisms of other relevant genes may predispose different ethnic groups to autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms of the ETS1 gene have been implicated in systemic lupus erythematosus (SLE) and coeliac disease (CD), which is also characterized by aberrant activation of the immune system (6)(7)(8)(9). ETS1 belongs to the ETS family of transcription factors (10).…”
mentioning
confidence: 99%
“…Th17 cells are associated with the production of mediators of inflammation; thus, they have potentially pathogenic roles in autoimmune disease. It has been shown that IL‐17–producing cells play a role in progression of SLE both in humans (4, 5) and in mouse models (6). Th17 cells produce IL‐6, TNFα, IL‐21, IL‐22, IL‐1β, and granulocyte–macrophage colony‐stimulating factor in addition to IL‐17A and IL‐17F (2).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of Th17 cells in rheumatoid arthritis (RA) has been explored (3). Furthermore, there is increasing evidence both in humans (4, 5) and in mouse models (6) suggesting that IL‐17–producing cells play a role in the progression of systemic lupus erythematosus (SLE).…”
mentioning
confidence: 99%
“…Our preliminary results showed that the T-cell lineage of NOD mice expresses the Ets1 gene at a level identical to that in T-cells in AKR mice and that there is no mutation in the Ets1 gene coding frame (unpublished data). However, it was reported that polymorphism in the 3Ј nontranslating region of Ets1 may be associated with autoimmune syndromes (47). The mechanisms of the NKT cell deficiency in NOD mice remain to be elucidated.…”
Section: Cd8mentioning
confidence: 99%